Legal Protection in Construction and Transfer Cooperation Between Surakarta Revenue Agency and Bank Mandiri’s EPPSON Program - Mindipurnama Putra, Ijlal Hanif; Wardiono, Kelik (Fakultas Syariah INSURI Ponorogo, 2025)
Local taxes are a vital source of revenue for Surakarta City, yet taxpayer compliance remains low due to payment procedures perceived as complex and inefficient. To address this issue, the Surakarta City Revenue Agency (Bapenda) implemented the Electronic Payment System Online (EPPSON) in collaboration with Bank Mandiri as part of its digital taxation and smart city initiative. This study examines the legal construction, regulatory framework, and legal protection of the cooperation agreement between Bapenda Surakarta and Bank Mandiri. Utilizing a normative empirical approach that incorporates legislative, socio-legal, and conceptual perspectives, the research examines both regulatory instruments and their practical implementation. The findings indicate that cooperation is structured through a non-cash local tax payment service under a Build, Transfer, and Operate (BTO) scheme, positioning Bank Mandiri as a strategic partner in fiscal digitalization. While EPPSON improves efficiency and accessibility, legal challenges persist, including contractual ambiguities, uneven data protection standards, and the absence of specific regional regulations governing digital tax payments. The program is legally grounded in Presidential Regulation No. 38 of 2015; however, strengthening derivative regulations and cybersecurity safeguards remains essential for its sustainability.